The theory on “eide” according to Nicholas of Methone - Terezis, Christos; Petridou, Lydia (Vox Patrum, 2018)
In this study, we are discussing the theory on “eide” and their relation to the “matter” according to Nicholas of Methone. This is a topic that shows the way in which God, as the supreme and only Principle, is connected to the natural world and human being. In this attempt of ours we move both historically and systematically. Thus, we first point out the differences on this issue between the ancient Greek thought, which moves towards dualism, and Christianity, which accepts only monism; we then explain the monistic reconstruction of the ancient Greek ontology by the Neoplatonists. Nicholas of Methone’s views and the Christian readings of ontology constitute the core of our approaches, of which it is highlighted that “eide” are the content of the divine Mind and that they are the good divine volitions. The question is also put in view of the unions and distinctions, since “eide” are a unified but internally differentiated whole in God. At the level of the sensible world, it is shown that “matter” is not considered independently from “eide”. The main conclusion that comes to the fore is that Nicholas of Methone makes a philosophical reading of the Christian theory on triune God’s energies, remaining consistent with Christian realism and rejecting the self-existent character of the “eide”.